2007
DOI: 10.4321/s0212-71992007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Utilidad del CMBD para la detección de acontecimientos adversos por medicamentos

Abstract: 3.2% of admissions was caused by ADEs. 2.2% of hospitalized patients experienced ADEs. 62% of ADEs were potentially preventable. A high proportion of preventable ADEs were around a small number of drugs. Effective safety practices directed to reduce the incidence of medication errors are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…four 10,11,14,30 did not provide information on the place where they were performed. Interestingly, 62.1% of the studies (18/29) 6,7,8,9,12,13,15,16,19,20,21,22,25,26,27,31,33,34 involved university, academic, or teaching hospitals, i.e., presumably large-scale, high-complexity hospital units.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…four 10,11,14,30 did not provide information on the place where they were performed. Interestingly, 62.1% of the studies (18/29) 6,7,8,9,12,13,15,16,19,20,21,22,25,26,27,31,33,34 involved university, academic, or teaching hospitals, i.e., presumably large-scale, high-complexity hospital units.…”
Section: Resultsmentioning
confidence: 99%
“…The filters consisted basically of rescue drugs, altered laboratory findings, or signs and symptoms related to adverse events. Thirtyeight per cent (11/29) 8,9,13,14,15,17,19,24,30,31,33 of the studies used patient chart review, while in four of these 12,14,30,31 the patient charts were only reviewed to confirm the events. Twenty-eight per cent (8/29) 6,14,21,23,24,25,29,30 of the studies identified the ICD codes related to the events, of which four studies used ICD-9 14,21,23,30 , three ICD-10 6,25,29 , and one the clinically modified ICD-9 24 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations